(untitled) (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2026)
Initial Public Offerings (IPOs) represent an important mechanism through which firms raise capital from public markets. A widely documented phenomenon in global financial markets is IPO underpricing, where shares are issued at a price below their market value, resulting in positive first-day returns for investors. This study investigates the extent of IPO underpricing and the long-term performance of selected Indian companies listed after 2010. A sample of fifteen companies across multiple sectors, including technology, financial services, retail, pharmaceuticals, and defence, was analyzed using publicly available market data. IPO underpricing was calculated as the percentage difference between the offer price and the listing-day closing price. Long-term performance was evaluated using one-year and three-year returns relative to the IPO offer price. Descriptive statistical methods, including mean and median comparisons, were employed to evaluate return patterns and distribution characteristics. The findings reveal an average IPO underpricing of 38.03%, indicating substantial listing-day gains in the Indian primary market. The average one-year and three-year returns were 40.69% and 114.84%, respectively. However, median returns were significantly lower, particularly for the three-year period (20.90%), suggesting that long-term gains are concentrated in a small number of high-performing firms. The results indicate that while IPO participation in India can generate meaningful short-term gains, long-term wealth creation is uneven and firm-specific. These findings contribute to the literature on IPO behavior in emerging markets and provide insights for investors, issuers, and policymakers.